ANALISIS BIAYA DAN WAKTU MENGGUNAKAN METODE EARNED VALUE MANAGEMENT (EVM) PADA PROYEK PEMBANGUNAN ARJUNO AGRO TECHNO PARK - Reky Muhamad Fairuz; Daimil Ihsan; Sucipto Sucipto (Matriks Teknik Sipil, 2025)
In construction project management, cost and time are two crucial, interconnected elements. Delays in project completion and cost increases are common issues that are often encountered. This research aimed to evaluate and control the cost and time of the Arjuno Agro Techno Park development project using the Earned Value Management (EVM) method. EVM is an integrated method that combines scope, cost, and time measurements to objectively assess project performance. The primary focus of this study was to identify cost and time deviations from the initial plan and determine the project's performance status at specific periods.The approach applied in this research was quantitative, involving data collection related to the Budget Estimate Plan, project schedule, and actual progress reports from the Arjuno Agro Techno Park project. The data was analyzed using EVM indicators such as, BCWS, ACWP, SV, CV, SPI, CPI, ETC, EAC, EAS, and ETS. The research findings indicated that the project experienced schedule delays, evidenced by an (SPI < 1) from the 7th to the 21st week. Nevertheless, the project was successfully completed in the 22nd week, which was initially targeted for completion in the 21st week. However, the project's completion cost tended to be more efficient compared to the initial contract value, as indicated by a (CPI > 1). Keywords: Arjuno Agro Technopark; Earned Value Management (EVM); project cost; project performance; project time